2015
DOI: 10.1177/003335491513000615
|View full text |Cite
|
Sign up to set email alerts
|

Zombie Apocalypse: Can the Undead Teach the Living How to Survive an Emergency?

Abstract: Objective. We examined whether or not CDC's zombie apocalypse campaign had the ability to achieve the agency's goals of educating young people about emergency preparedness and prompting them to get ready by developing an emergency kit and plan. While the campaign was extremely popular, we examined the question of whether the campaign had the capability to translate into knowledge and action.Methods. We conducted an online experiment with 340 undergraduate students divided randomly into two groups. One group wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…One option could have been the generation of fictional problems -potentially quite extreme ones. However, as the Zombie Preparedness initiative from the US Centres for Disease Control and Prevention (CDC) demonstrated that novelty and high engagement with fictional scenarios may not translate into long-term change (see CDC, 2017;Kruvand and Silver, 2013;Kruvand and Bryant, 2015;Fraustino and Ma, 2015). While the CDC campaign was aiming to affect change in end users, not build practitioner capacity, it indicates that some caution is needed.…”
Section: Interdisciplinary Problem-based Learningmentioning
confidence: 99%
“…One option could have been the generation of fictional problems -potentially quite extreme ones. However, as the Zombie Preparedness initiative from the US Centres for Disease Control and Prevention (CDC) demonstrated that novelty and high engagement with fictional scenarios may not translate into long-term change (see CDC, 2017;Kruvand and Silver, 2013;Kruvand and Bryant, 2015;Fraustino and Ma, 2015). While the CDC campaign was aiming to affect change in end users, not build practitioner capacity, it indicates that some caution is needed.…”
Section: Interdisciplinary Problem-based Learningmentioning
confidence: 99%
“…The case studies contrasted with more fantastic scenarios, such as the US CDC's Zombie preparedness initiative public engagement campaign (including resources for school children) (CDC, 2017, campaign originally run in 2011). Although the Zombie campaign was an imaginative and popular cross-media exercise, it was difficult to identify marked changes in behaviour by those who engaged with it and later studies conducted with the material indicated no long term change in participant behaviour around risk preparedness (Kruvand, Silver, 2013, Kruvand, Bryant 2015, Fraustino, Ma, 2015. While the Zombie campaign was focused on public engagement, not building capacity for practitioner skills, the follow up research listed above highlights the dangers of fictional scenarios, and especially the use of humour.…”
Section: Design In the Workhopmentioning
confidence: 99%
“…One option could have been the generation of fictional problemspotentially quite extreme ones. However, as the US CDC's Zombie preparedness initiative demonstrated, novelty and high engagement with fictional scenarios may not translate into long term change (see CDC, 2017 for the original campaign, and Kruvand, Silver, 2013, Kruvand, Bryant 2015, Fraustino, Ma, 2015 for follow up research on its effectiveness). While the CDC campaign was aiming to affect change in end https://doi.org/10.5194/gc-2019-9 Preprint.…”
Section: Interdisciplinary Problem Based Learningmentioning
confidence: 99%